2022
DOI: 10.1177/02676591221113135
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of survival in patients on extracorporeal membrane oxygenation therapy due to severe covid-19

Abstract: Background Severe acute respiratory distress syndrome (ARDS) due to Coronavirus Disease-19 (COVID-19) is associated with high mortality. Although survival on mechanical circulatory support has improved, determinants for better prognosis are still unclear. Here, we report on the outcome of our patient population with the need for mechanical circulatory support due to severe COVID-19 (sCOVID-19) induced ARDS. Methods All patients treated with extracorporeal membrane oxygenation (ECMO) for severe ARDS due to sCOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…While the ELSO registry reported mortality of approximately 40% for VV ECMO patients in 2020, recent large single-institution studies have shown much greater variability. These reports have ranged from 54% mortality in France18, 50% in Germany22, 22 46% in Italy26, 26 74% in Poland27, 27 and 60% at our center. Differences in patient characteristics during various pandemic periods may explain the heterogeneity of published ECMO-associated outcomes.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…While the ELSO registry reported mortality of approximately 40% for VV ECMO patients in 2020, recent large single-institution studies have shown much greater variability. These reports have ranged from 54% mortality in France18, 50% in Germany22, 22 46% in Italy26, 26 74% in Poland27, 27 and 60% at our center. Differences in patient characteristics during various pandemic periods may explain the heterogeneity of published ECMO-associated outcomes.…”
Section: Discussionmentioning
confidence: 65%
“…A recent German study of COVID-19 ECMO patients found that renal failure was much more common among non-survivors compared to survivors at 73% versus 33% (p < 0.001). 22 In addition, data from France also found that patients with a lower renal component of the Sequential Organ Failure Assessment (SOFA) score pre-ECMO had a lower risk of mortality.18 Although dialysis can easily be provided to patients while on ECMO, pre-cannulation renal failure may signify greater systemic disease severity and affect prognosis. There is insufficient evidence to include renal failure as a contraindication to ECMO, but like older age, it should be considered in the presence of other adverse prognostic factors, especially if resources are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Of these articles, seventeen cohorts reported the time from symptom onset to ECMO [22,24,26,31,39,40,42,44,50,[54][55][56]61,63,65,67,70], four reported the time from COVID-19 diagnosis to ECMO [34,38,47,52], eleven reported the time from hospital admission to ECMO [20,24,25,39,42,46,48,61,64,66,71], four reported time from ICU admission to ECMO [23,29,44,61], thirty-nine reported time from intubation or MV to ECMO [19,24,[26][27][28][29][30][33][34][35][36][37][38]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the total articles, twentyfour studies were conducted in the Americas (twenty-two in the United States of America (USA) [19][20][21]24,25,32,34,35,38,39,46,47,52,54,55,57,58,61,65,66,68,70], one in Argentina [26], one in Chile [29]), twenty-three in Europe (nine in France [22,29,33,42,44,49,50,59,60], six in Germany [31,37,41,48,62,71], two in the United Kingdom of Great Britain and Northern Ireland (UK) [27,72], two in Spain [51,56], one in Finland [23], one in Austria [36], one in Poland [64], one in Italy [45]), seven in Asia (three in China [28,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation